Rapid progression of disease in two cases of undifferentiated endometrial carcinoma - Krista S. Pfaendler; Leslie M. Randall (Elsevier, 2019)
Undifferentiated endometrial carcinoma, a rare histopathologic diagnosis, has a poor prognosis with high risk of progression during or shortly after completion of adjuvant treatment. We present two cases of undifferentiated endometrial carcinoma: one in a postmenopausal female who experienced recurrent disease immediately after completion of adjuvant treatment and one in a premenopausal female who experienced disease progression while receiving adjuvant treatment. These cases exemplify the aggressive behavior of undifferentiated endometrial carcinoma and suggest the need for a more effective treatment in the upfront setting than the current standard of care for endometrioid endometrial adenocarcinoma. Keywords: Undifferentiated endometrial carcinoma, Endometrial cancer, Dedifferentiated endometrial carcinoma